Study on Database Management System Security Issues - Mohd Amin Mohd Yunus; Sonniaa K.V. Gopala Krishnan; Nazri Mohd Nawi; Ely Salwana Mat Surin (JOIV : International Journal on Informatics Visualization, 2017)
The study is about the security system of database management (DBMS) and proposed method. Information is an essential element in database management system where the users trust service providers will have a secure system to protect and prevent their information from malicious attack or stealing information. There are few types of technique applied to enhance the database security level.Â Â